Evaluation of chemical and bio-control agents for management of Cedrus deodara root rot caused by Phytophthora cinnamomi - ASHWANI TAPWAL, LAL SINGH*, MANINDER JEET KAUR (Indian Phytopathology, 2010)
Phytophthora cinnamomi was identified as the cause for drying up of deodar (Cedrus deodara) in the North- Western Himalayas. 50mg/ml concentration of Ridomil MZ was observed to inhibit the complete growth of P. cinnamomi in vitro. The impact of Ridomil MZ application on soil fungi revealed decrease in their population after 15 days of application but regained almost the original status within 30 days suggesting no lethal impact to the friendly rhizosphere fungi. Trichoderma spp. were observed as the most effective antagonists against P. cinnamomi among the associated fungal flora of C. deodara rhizosphere. The volatile compounds of the tested antagonists inhibited the growth of pathogen to a lesser extent as compared to dual culture. The application of the Ridomil MZ was identified as one of the immediate measure to control P. cinnamomi.